Tensile behavior of high-strength strain-hardening cement-based composites (HS-SHCC) made with high-performance polyethylene, aramid and PBO fibers. (August 2017) - Curosu, Iurie; Liebscher, Marco; Mechtcherine, Viktor; Bellmann, Cornelia; Michel, Stefan
Abstract: The article at hand presents an investigation of the tensile behavior of high-strength strain-hardening cement-based composites (HS-SHCC) made with four different types of dispersed high-performance polymer fibers. In particular, high-density polyethylene (HDPE), poly( p -phenylene-terephthalamide) (aramid), as-spun poly( p -phenylene-2, 6-benzobisoxazole) (PBO) and high-modulus PBO fibers were examined in respect of their reinforcing effect in a high-strength, finely grained, cementitious matrix. Besides the tension experiments at the composite level, single fiber pullout tests were performed for a micromechanical characterization of each composite material. Furthermore, contact-angle measurements and microscopic investigations were carried out to assess the fibers' ability to be wetted and to explain their interaction with the cementitious matrix.